Model Lintnera na polskim rynku kapitałowym - Pietrzak, Tomasz; Wójcikowski, Rafał (The Lintner model on the Polish market, 2006)
The Lintner model, also called partial adjustment model, has been successfully tested for 50 years on numerous world markets, both developed and emerging ones. The article is an attempt to verify the model on the Polish market. The estimations confirm the model holds and earnings best explain the dividend changes. Positive empirical model verification is significant not only for investors applaying it to anticipate future dividends, but also for equity valuation in DCF models based on future dividends and their growth rate (such as Gordon model).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 384-391